Cardiofacio-cutaneous syndrome: Classical presentation of a rare genodermatoses - Mahesh Prajapat; Sunil K Kothiwala; Mohit Sharma; C M Kuldeep (Wolters Kluwer Medknow Publications, 2016)
Cardiofacio-cutaneous syndrome is a rare genodermatoses with multiple congenital anomalies (MCA) and mental retardation. Although various mutations have been described, the diagnosis can be made clinically based on constellation of symptoms. Herein, we report a classical case with typical craniofacial features and atrial septal defect.